Explicit Connection Actions in Multiparty Session Types - Hu, Raymond; Yoshida, Nobuko (Fundamental Approaches to Software Engineering, 2017)
This work extends asynchronous multiparty session types (MPST) with explicit connection actions to support protocols with optional and dynamic participants. The actions by which endpoints are connected and disconnected are a key element of real-world protocols that is not treated in existing MPST works. In addition, the use cases motivating explicit connections often require a more relaxed form of multiparty choice: these extensions do not satisfy the conservative restrictions used to ensure safety in standard syntactic MPST. Instead, we develop a modelling-based approach to validate MPST safety and progress for these enriched protocols. We present a toolchain implementation, for distributed programming based on our extended MPST in Java, and a core formalism, demonstrating the soundness of our approach. We discuss key implementation issues related to the proposed extensions: a practical treatment of choice subtyping for MPST progress, and multiparty correlation of dynamic binary connections.